Sustainability of Baba Nyonya cultural heritage tourism - Amalina Zainal, 1992-, author 618867 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2018)
Thesis (Sarjana Pengurusan (Teknologi)) - Universiti Teknologi Malaysia, 2018